2019
DOI: 10.1002/aws2.1131
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of point‐of‐use/point‐of‐entry systems to remove per‐ and polyfluoroalkyl substances from drinking water

Abstract: The contamination of groundwater sources with per- and polyfluoroalkyl substances (PFAS) in the United States is a widespread problem for the drinking water industry. Well water supplies in the municipalities of Fountain, Security, and Widefield, Colorado, contain perfluorooctanoic acid and perfluorooctane sulfonate levels greater than the U.S. Environmental Protection Agency (USEPA) health advisory level of 70 ng/L. The source of PFAS has been associated with aqueous film-forming foam at Peterson Air Force Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 7 publications
1
25
1
1
Order By: Relevance
“…Existing research focuses on treating PFOA and PFOS (Meng et al, ; Yang et al, ; Yu et al, ; Zhi & Liu, , ), often using model waters spiked with one or more PFAS compounds at equal concentrations, commonly at higher concentrations than detected in groundwaters used as drinking water supplies. Only a few comparative PFAS removal studies exist in continuous‐flow adsorption systems in real groundwaters with ambient PFAS concentrations and ratios (Liu, Werner, & Bellona, ; Patterson et al, ; Schaefer, Nguyen, Ho, Im, & LeBlanc, ; Woodard, Berry, & Newman, ; Xiao et al, ; Zaggia et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Existing research focuses on treating PFOA and PFOS (Meng et al, ; Yang et al, ; Yu et al, ; Zhi & Liu, , ), often using model waters spiked with one or more PFAS compounds at equal concentrations, commonly at higher concentrations than detected in groundwaters used as drinking water supplies. Only a few comparative PFAS removal studies exist in continuous‐flow adsorption systems in real groundwaters with ambient PFAS concentrations and ratios (Liu, Werner, & Bellona, ; Patterson et al, ; Schaefer, Nguyen, Ho, Im, & LeBlanc, ; Woodard, Berry, & Newman, ; Xiao et al, ; Zaggia et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, RO provides excellent removal of PFAS (Glover et al, 2018; Patterson et al, 2019); even nanofiltration has been shown to be highly effective (Steinle‐Darling et al, 2010). The feasibility of implementing an RO‐based treatment solution depends heavily on site‐specific conditions for brine disposal, and its implementation may be associated with relatively high construction and operating costs.…”
Section: Introductionmentioning
confidence: 99%
“…PFAS are well removed through various separation methods such as granular activated carbon (GAC), ion exchange (IX), or nanofiltration/reverse osmosis (NF/RO) membranes (Belkouteb et al 2020;Kim et al 2020;Li et al 2020;Rodowa et al 2020;Ateia et al 2019a, b;Boone et al 2019;Page et al 2019;Patterson et al 2019;Wei et al 2019;Hopkins et al 2018;Schaefer et al 2018;McCleaf et al 2017;Zaggia et al 2016;Appleman et al 2014;Rahman et al 2014). Gagliano et al (2020) reviewed the removal of long-and short-chain PFAS by adsorption and noted that the adsorption capacity of short-chain PFAS is lower than that observed for long-chain PFAS.…”
Section: Removal Through Drinking Water Treatmentmentioning
confidence: 99%